Impact of quality control indicator system management program on neoadjuvant and adjuvant therapies for breast cancer: a comparative analysis - Xu, Silu; Ding, Nianyang; Zhang, Lili; Hu, Sainan; Ni, Meixin; Gu, Haijuan; Chen, Zeng; Xie, Zhengzheng; Wu, Nan; Wen, Yuanyuan; Fang, Panqi; Liu, Xin; et al. (Frontiers in Oncology, 2026)
BackgroundBreast cancer (BC) management in China faces significant challenges, particularly in terms of standardizing diagnosis and treatment protocols across various healthcare settings. The implementation of a quality control (QC) indicator system offers a potential solution to improve treatment consistency and outcomes. This study evaluated the impact of a QC indicator system on the standardization of neoadjuvant and adjuvant therapies for BC.MethodsA QC system was developed by an expert panel in alignment with China’s 2022 guidelines. A comparative study was conducted between Jiangsu Cancer Hospital (experimental, implementing PDCA-cycle management) and Nantong Tumor Hospital (control, routine practices). Key indicators included cTNM staging completeness, chemotherapy record standardization, and rational anti-tumor drug use. Additionally, clinical outcomes, patient-reported outcomes (PROs), and treatment adherence were assessed, alongside qualitative data derived from clinical records.ResultsAfter the QC system was implemented, Jiangsu Cancer Hospital demonstrated significant improvements: cTNM staging completeness increased from 92.5% to 98.08%, chemotherapy record standardization improved by 66.65%, and rational drug use rose from 78% to 87.5% (all P<0.05). In contrast, no significant improvements were observed in the control hospital. The clinical outcomes and patient-reported symptoms also demonstrated favorable trends in the intervention hospital. Qualitative data revealed facilitators such as clearer treatment protocols and improved coordination, while challenges included increased documentation workload.ConclusionsThe QC system effectively enhanced the standardization of neoadjuvant and adjuvant therapies for breast cancer, with improvements in clinical management and rational drug use. These results offer a scalable model for improving breast cancer management quality in other regions and institutions. Further research, including multi-center studies with extended follow-up, is recommended to validate these findings and explore the long-term impact of QC interventions on patient outcomes.